HUBUNGAN ANTARA KEPRIBADIAN EKSTRAVERSI DENGAN KEPUASAN PERKAWINAN PADA KARYAWAN WANITA DI PT INDOTAMA OMICRON KAHAR PURWOREJO - Eny Intan Sari; Yeniar Indriana; Jati Ariati (Jurnal EMPATI, 2012)
Married women employees who have children prone to excess role, especially in such type of jobs with low level, tight schedules and less autonomy (Marshall in Berk, 2010, p.494). the conflicts required an individual’s ability to cope. One of the factors that affect is personality. Individuals with high extraversion have good social skills, more assertive and cooperative to be able to manage relationship better (Argyle & Lu in  Argyle, 2001, p.75). the aims of this study is ti investigate empirically relationship between extraversion and marital satisfaction of married women employees in PT Indotama Omicron Kahar and the effective contribution of extraversion on marital satisfaction.Sample of this study was 68 married women employees obtained by accidental sampling. Data collection methods using two scales, Marital Satisfaction Scale and Extraversion Scale. The marital satisfaction scale consist of 40 items (α=0,882) and extraversion scale consist of 25 items (α=0,826). Analysis of data using simple regression analysis.Results of this study showed a correlational coefficient (rxy) of 0,308 with p=0,011 ( p<0,05) indicating positive relationship between extraversion and marital satisfaction, higher extraversion, the higher perceived marital satisfasction. Contribution of extraversion personality on marital satisfaction was 9.5% and the rest is influenced by other factors.